PENGARUH PENERAPAN MODEL PEMBELAJARAN TALKING STICK DISERTAI HANDOUT TERHADAP HASIL BELAJAR BIOLOGI SISWA KELAS VII SMPN 1 SUNGAI RUMBAI KABUPATEN DHARMASRAYA - Dwikirana, Fani; Sudirman, Sudirman; Widiana, Rina (STKIP PGRI Sumbar, 2013)
ABSTRACTThe background of this research are the thought very boring biology class, so students are less active and less motivated to learn. This causes students to be low biological value, with the average value obtained is still below minimum completeness criteria (KKM) set of 75. Therefore, the role of teachers make lessons interesting biology into lessons, one of which apply the learning model talking stick with handouts. This study aimed to determine the effect of application of learning models talking stick with handouts on learning outcomes biology class VII SMPN 1 Sungai Rumbai Dharmasraya. This study was conducted in May 2013. This type of research is experimental research, the research design Randomized Control Group Posttest Only Design. The population in this study were all students of class VII SMPN 1 Sungai Rumbai second semester of the school year 2012/2013. The sample in this study is VIIA and VIIB grade students, who were taken by using Simple Random Sampling technique, while to determine the experimental class and the control class conducted the draw, so the derived class as the experimental class VIIB and control class VIIA. The instrument used in this study is a student achievement test as many as 38 items objective. From the results of experimental studies have shown that the class average score (82.03), higher than the control class (76.91). Of the t-test analysis t obtained (2.95) > t table (1.67) so it can be concluded that the model of learning with instructional handouts talking stick with biology to improve learning outcomes of students of class VII SMPN 1 Sungai Rumbai Dharmasraya.Â